Reforming the institutional and legal frameworks of E - commerce in Kenya; consumer rights protection in the digital economy - Gitari, Silas Mbogo (Strathmore University, 2020)
Electronic commerce (E-commerce) is fast growing in Kenya, attributable to improved internet accessibility and increased usage of smart phones. The use of E-commerce has spurred growth and created new opportunities for entrepreneurs, especially the small and medium-sized businesses, which can operate with reduced initial investment and set up costs. Its other benefits to entrepreneurs and consumers include reduced transaction costs, convenience of flow of information and movement of goods, better coordination of activities between manufacturers, suppliers and customers as well as instant access to worldwide markets among others. Despite the foregoing benefits, Kenya is yet to formulate an effective legal and institutional framework that protects consumer rights. Such a regime should afford the consumers transparency, through information disclosure and verification, data privacy and protection, conformity of the goods to the required quality standards and opportunity for redress, in a similar fashion to the consumer rights protection afforded in other traditional forms of commerce. Under the current regime, there is potential for abuse, especially because there is no personal interactions between the consumers and the vendors or an opportunity to inspect the goods or service prior to contracting. The multi-jurisdictional nature of E-commerce also makes it challenging for dispute resolution and consumer redress. Internationally, policies, legislations, regulations and laws have been/ are being enacted to address the various consumer rights concerns in E-commerce. Kenya should thus follow suit. This thesis sets out a conceptual framework and analyses the existing legal and institutional regime in Kenya, relating to consumer rights protection in E-commerce. Through a comparative study with South Africa, it shall assist identify the gaps in the Kenyan regime and make proposals for reform.
A Thesis submitted in partial fulfillment of the requirements of the Degree of Master of Laws, at Strathmore University
Keywords: Legal frameworks; E - commerce_Kenya; Consumer rights protection